Exploring the Influence of Marketing Content and Customer Engagement on Culinary Purchase Intentions : Evidence from @sigerfoodies' Followers in Bandar Lampung - Osya Annisa Salsabila; Roslina Roslina; Aripin Ahmad (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
In today's increasingly competitive digital business environment, entrepreneurs must develop smarter and more effective marketing strategies to promote their products. Food vloggers play a pivotal role by influencing their followers through social media content, particularly culinary reviews and personal experiences with food products, which encourage followers to purchase the recommended items. This study investigates the impact of marketing content and customer engagement on the purchase intentions of followers of the @sigerfoodies Instagram account. Using a quantitative research approach, data were collected through questionnaires, employing a non-probability sampling method with a purposive sampling technique. The sample consisted of 140 respondents. Data analysis, including instrument validity, normality tests, multiple linear regression, and hypothesis testing, was conducted using SPSS 26. The findings indicate that both marketing content and customer engagement of @sigerfoodies significantly and positively affect the purchase intentions of culinary products in Bandar Lampung. To enhance its influence, Sigerfoodies is encouraged to organize giveaways, share engaging culinary facts, and foster interactions with followers to strengthen long-term relationships.